The Effect of Remittances on Labour Supply in the Republic of Haiti - Evans Jadotte; Xavi Ramos (Institute for the Study of Labor (IZA), 2015)
We examine the labour supply effect of remittances in the Republic of Haiti, the prime international remittances recipient country in the Latin American and Caribbean (LAC) region relative to its GDP. Unlike previous empirical literature we address three econometric issues that may bias the estimates. We account for endogeneity of the remittances with respect to labour supply, for the zero-inflated nature of our dependent variable, hours of work, and for the self-selection of the migrant sample. Our results are in line with previous literature, and point to a decline of labour supply in the presence of remittances. However, contrary to previous findings, the labour market response to remittances of female household heads is not as sensitive as male's.
Keywords: C39; F22; F24; J22; 330; international migration; remittances; labour supply; Republic of Haiti